Characterization, antioxidant activity, and biocompatibility of selenium nanoparticle-loaded thermosensitive chitosan hydrogels. Issue 10 (3rd July 2021) - Wu, Lingying; Wu, Yuling; Che, Xun; Luo, Dandan; Lu, Jiaju; Zhao, Ruibo; Zubair Iqbal, Muhammed; Zhang, Quan; Wang, Xiumei; Kong, Xiangdong
Abstract: In this study, we recruited chitosan (CS) both for selenium nanoparticles (SeNPs) synthesis and for the development of a thermoresponsive nanocomposite hydrogel with the addition of glycerol phosphate (GP). Considering that SeNPs are toxic at high concentrations, five different ingredients of the nanocomposite hydrogel system with low concentrations of SeNPs (1.25–20 μg/mL) were prepared. The gelation conditions, structural characteristics, and mechanical properties of SeNPs-loaded thermosensitive CS/GP hydrogels were investigated. We also evaluated their antioxidizing activities and biocompatibility of the CS/GP/SeNPs hydrogels. Our study demonstrated that the incorporation of SeNPs in the hydrogel improved its mechanical properties, antioxidant activity, and degree of swelling. According to the properties of SeNPs and CS/GP thermosensitive hydrogels, the combination of these two technologies in an appropriate manner would be a promising antioxidant system for drug delivery and tissue engineering.